Barriers to Therapeutic Use of Hydroxyurea for Sickle Cell Disease in Nigeria: A Cross-Sectional Survey - Okocha, Emmanuel Chide; Gyamfi, Joyce; Ryan, Nessa; Babalola, Oluwatoyin; Etuk, Eno-Abasi; Chianumba, Reuben; Nwegbu, Maxwell; Isa, Hezekiah; Madu, Anazoeze Jude; Adegoke, Samuel; Nnebe-Agumandu, Uche; Brown, Biobele; et al. (Frontiers in Genetics, 2022)
Background: Sickle cell disease, the inherited blood disorder characterized by anemia, severe pain and other vaso-occlusive complications, acute chest syndrome, disproportionate hospitalization, and early mortality, has significant financial, social, and psychosocial impacts and drains individuals, families, and health systems globally. Hydroxyurea could improve the health of the 300,000 individuals born each year with sickle cell disease in sub-Saharan Africa; however, challenges to adoption and adherence persist. This study assessed the barriers to therapeutic use of hydroxyurea for sickle cell disease within the Nigerian healthcare system, specifically from the level of the patient, provider, and health system. Methods: We used purposive sampling to recruit participants from 13 regions in Nigeria. A cross-sectional survey was administered to physicians (n=70), nurses or counselors (n=17), and patients or their caregivers (n=33) at 13 health centers. Findings were mapped onto the appropriate Consolidated Framework for Implementation Research (CFIR) domains. Results: This study was able to identify factors that mapped onto the inner setting, outer setting, and characteristics of individuals domains of CFIR. The majority of physicians (74.3%) prescribe hydroxyurea, and half stated hydroxyurea is the standard of care. Among clinicians, barriers included limited knowledge of the drug, as well as low self-efficacy to prescribe among physicians and to counsel among nurses; perceived side effects; perceived patient preference for traditional medicine; cost for patient and expense of accompanying laboratory monitoring; and limited availability of the drug and equipment for laboratory monitoring. Among patients and caregivers, barriers included lack of knowledge; perceived side effects; cost; religious beliefs of disease causation; and lack of pediatric formulation. Conclusions: Findings suggest that patient, provider, and health systems-level interventions are needed to improve hydroxyurea uptake among providers and adherence among patients with sickle cell disease in Nigeria. Interventions such as patient education, provider training, and policy change could address the disproportionate burden of sickle cell disease in sub-Saharan Africa and thus improve health equity.